Digital Revolution: Europe at the Lead of New Technologies - Irimie, Rada Cristina (European Journal of Social Science Education and Research, 2014)
The pace and scope of changing technologies are constantly challenging social structures and the need for dexterous policy framework is becoming more and more indispensable. While technological evolution and market forces have driven the information and communication revolution, the European Union has played a significant role in creating an effective framework for the maintenance and development of this progress. In order to regulate the market and keep pace with the ICT (Information and Communications Technology) environment, the EU has introduced rules that ensure fair access to all EU citizens and stimulate competition for companies. The Body of European Regulators for Electronic Communications (BEREC) serves entirely this function, becoming a pan-European regulatory agency. Aside the regulatory role, EU’s economic growth strategy involves a great number of policies and measures to capitalize on digital revolution. The Digital Agenda for Europe (DAE) targets not only on citizens, but businesses of Europe as well, to benefit from the technological revolution. The former and the new goals of the renewed agenda raise the bar of smart, sustainable and inclusive growth. Finally, to ensure the maximization of use of information technologies, EU has supported the expansion of e-business and online public services. E-government services have facilitated interaction between government, citizens and businesses, while it simplified all facets of operations of governmental organisations. This article is looking at EU’s role in digital environments, examining the three initiatives as platforms of technological evolution in Europe. The three case studies used, the BEREC, DAE and e-Government initiatives, will provide an analysis of the services with a prospective evaluation of the technological strategies involved, while the qualitative and quantitative data in each case will help us analyse the quota and draw conclusions on the functionality and effectiveness of the services. We expect to evaluate the levels of digital growth and online adaptation of the Union and/or the need for further expansion. The study is discussing EU’s technological competiveness and the analysis targets the policy initiatives taken towards this direction, while it provides multipolar, but useful information for EU citizens and businesses.